Rapid dot-immunobinding assay on nitrocellulose for viral antibodies. - Heberling, R L (1986)
A procedure is described for the routine laboratory diagnosis of viral serum antibodies. Antigens are dotted on nitrocellulose strips or sheets, and sera are applied on absorbent paper strips. Antigen-antibody complexes are detected with enzyme-conjugated antiglobulin and development of a colored, insoluble substrate product. The test allows processing of multiple sera in one 3- to 5-h operation and is equal to or more sensitive than serum neutralization, hemagglutination inhibition, and fluorescent antibody assays. Highly infectious viruses inactivated with a psoralen derivative and long-wavelength UV light irradiation can be used as antigens, allowing the study of human pathogens. Although the test detects cross-reacting, group-specific herpesvirus antigens, the intensity of the antibody reaction is greatest with type-specific antigens. Preliminary data suggest that the technique will be useful for the rapid typing of viruses from clinical specimens.